Group Investigation Modelin Teaching and LearningWriting for Secondary Level Students - Yepi Sedya Purwananti (EDUTEC : Journal of Education And Technology, 2019)
Group investigation is able to make the students involved from the planning, writing, until the completing of writing, both in determining the topic as well as a way to learn through investigation. One thing that differentiates it from other cooperative learning model is the model has a major focus group investigation of an object or topic to write. The investigation has provided opportunities for students to argue, think critically, do the findings and analyze collaboratively. The use of this model will also allow students to achieve success in learning, thinking skills and social skills. This learning model allows students to develop the knowledge, abilities, and skills totally in a learning environment that is open and democratic. Students are no longer as an object of learning, but can also act as tutors for their peers. The application of the model group investigation in writing class that implements the practice of speaking directly, authentic and natural is in line with efforts to improve and develop characters. Natural context in learning writing makes the learning process designed more meaningful. Learning to write by using a theoretical model of group investigations involving students in planning, exploring and sharing ideas. Students are encouraged to collaborate with friends and learn the "how" of their own in accordance with the cognitive style of each. Students empowered as the learners are able to argue, work hard, share, help peers, and have affection to friends.